Population-level Outcomes of Ex-Vivo Lung Perfusion (EVLP) in Lung Transplantation - Perez-Castro, Pablo; Bush, Errol; Haut, Elliott; McGready, John; King, Betsy (The Thoracic and Cardiovascular Surgeon, 2025)
Ex-vivo lung perfusion (EVLP) is a novel organ preservation technique introduced to assess extended lung donors and determine their suitability for human use.This retrospective cohort study analyzed lung transplant recipients in the U.S. from 2011 to 2021, using data from the Scientific Registry of Transplant Recipients (SRTR). Kaplan-Meier curves were used for time-to-event survival analysis, and the Cox proportional hazards model was used to determine hazard ratios for overall survival.Of 23,261 patients, 608 had EVLP-donor lungs. The 5-year survival was similar across groups. Centers with EVLP access had median wait times of 48 days (SD 260.80) versus 68 days (SD 273.73) at other centers. Cox proportional hazards model showed no significant disparity in 5-year survival with EVLP (HR 1.14, p 0.08), gender (HR 1.04, p 0.07), and high volume (HR 0.8, p 0.07). Perioperative extracorporeal membrane oxygenation (ECMO) (HR 1.29, p < 0.01) and black recipient race (HR 1.15, p < 0.01) influenced survival; there were no statistical differences in any other race. Black EVLP-assessed recipients showed a nonsignificant trend toward a survival benefit (p = 0.26) with a 14.2% higher 5-year survival (95% CI 2.7–28.7).EVLP has not adversely affected 5-year survival rates in lung transplantation recipients and is associated with shorter wait times. A survival advantage in black recipients with EVLP-assessed lungs needs further research.
Keywords: transplantation; lung; organ preservation; transplantation; heart–lung; surgery/incisions; surgery; complications